PERLINDUNGAN HUKUM BAGI PEKERJA RUMAH TANGGA DI BANDAR LAMPUNG - muhtadi, muhtadi (Lampung University, 2014)
abstractThis research which is a grant of DIPA UNILA 2013 aims to describe the rights of domestic workers as well as models of legal protection for them in Bandar Lampung. By using a normative approach based on secondary data, it can be concluded that first, the rights of household workers are the same as in other sectors, the difference lies only in its job type, and secondly, a model of protection of household workers is done by means of preventive and repressive. Protection model preventively done by providing the local regulations that give legal certainty to the position of household workers, including the obligations of the agreement between workers and employers, while repressive carried out by means of law enforcement, both the penal or civil code. The penal code is carried out as a responsibility of the State to prosecute and/or punish the employer and / or the person in the house that his actions resulted in physical injury and/or psychological. While civil law is an effort to provide workers rights which are not fulfilled in accordance with the employment agreement. It is recommended that in order to ensure legal certainty of the fulfillment of the rights of household workers in Bandar Lampung; it required legal norms that specifically governs the relationship of household workers and their employers in the form of local regulations.Â Keywords: Legal Protection, Right and Household Workers.